The efficiency of virtual learning environments based on social knowledge construction on learners' achievement and attitudes - Atici, Buenyamin (Turkish Education Assoc, 2007)
The aim of this study is to determine the efficiency of virtual learning environments based on social knowledge construction on learners' achievement and attitudes. In this direction, this study tried to compare the virtual learning environments based oil social knowledge construction With traditional learning environments in the course titled Human Development and Learning. The second year students who attended Human Development and Learning course at Firat University, Faculty of Technical Education, during the fall semester of 2002-2003 school year participated in the research. The pre-test and post-test control group research design was used in the study. The Study included three groups, each consisting of 24 members. The first experimental group acted only in virtual learning environments based on social knowledge construction, the second experimental group acted both in virtual learning environments based on social knowledge construction and traditional learning environments, and the control group acted only in traditional learning, environments. The major findings in this study indicated that; the students in the experimental group were found more successful considering the average opoints of the post-test. Both of thee experimental groups were more successful than the control group at the comprehension level. This study exposed positive findings of the virtual learning environments based on social knowledge construction about learning and teaching. It can be recommended that it is important to give learners more initiative under less control. It can be Said that it will be useful to implement courses such as literature, sociology, history, and philosophy in this environment in order to determine its efficiency from different points.
Keywords: virtual learning environments based on social knowledge construction; computer mediated communication; online learning communities; constructivism